OPTIMALISASI PENJADWALAN PERBAIKAN KAPAL DI PT X PADA PROYEK Y DENGAN CRITICAL PATH METHOD - Husin, M. Husin As ari; Akmal Suryadi (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
In the shipyard industry, the results of work often differ from the initial plans, including in the scheduling of ship repairs. Therefore, a method is needed to optimize the planning of shipyard projects. One approach used is network planning or network diagrams, which serve to determine the critical path (CP) of the tasks being performed. This method facilitates work network planning and identifies tasks that are part of the critical path. This study aims to identify the critical path of the broken-down tasks and to calculate labor acceleration, resource allocation, and the required costs. This method is applied to optimize the ship repair schedule at PT X for Project Y using the Critical Path Method (CPM) supported by Microsoft Project. In the bottop hull area, the initial work duration of 7 days was reduced to 5 days after crashing. The productivity calculation focuses on the bottop hull area, as this task has a clear and fixed unit of measurement, namely m². The research results show that the productivity index before crashing was 18 m²/person per day, with a productivity cost of Rp. 4,166.67/m²/person. After adding 2 workers, the distribution of labor became more even, although the productivity per person decreased to 15.12 m²/person per day. The productivity cost also increased to Rp. 4,960.31/m²/person.